Patent landscape report on inventions based on Plant Genetic Resources for Food and Agriculture (PGRFA) and Related Digital Sequence Information Genetic Sequence Data (DSI/GSD). Executive summary [ENG/FR/SP] - Chiarolla, Claudio; Kock, Michael A; Oldham, Paul; Halewood, Michael; Lopez Noriega, Isabel; Kindness, Jasmine (2025)
This report provides the first comprehensive patent landscape analysis of inventions based on Plant Genetic Resources for Food and Agriculture (PGRFA) and related Digital Sequence information (DSI) / Genetic Sequence Data (GSD). It examines how patents—especially those claiming naturally occurring (“native”) traits—may restrict subsequent research, breeding, and utilization of PGRFA. The study aims to support policy deliberations under the FAO International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty) in the lead up to the adoption of a comprehensive package of measures to enhance the functionality of the Multilateral System (MLS) of Access and Benefit Sharing at the Eleventh Session of the Governing Body. We identified 399 patent documents (first filings)—representing a relatively small percentage of the overall global patent activity as captured through the most relevant PGRFA indicators—that have the potential to limit the use of PGRFA materials from which these inventions were derived in further research and breeding. Based on the analysis of the claims in these patent families, we identified twelve types of claims that have medium to high potential to affect the relevant restrictions. However, we were unable to assess the extent to which materials from the Multilateral System (MLS) of the FAO Plant Treaty were used in the development of these patented inventions. The current legal and technical features of the data architecture of the international patent system do not make it possible to assess how many patents have been applied and/or granted for inventions that incorporate, or are based on, PGRFA materials from the MLS. We identify options that Contracting Parties to the Treaty could consider in order to address the issues raised in this report, including means to ensure ‘findable’ disclosures of MLS materials in patent filings, and suggest further analysis and/or guidelines, to be developed by the Technical Advisory Group on the MLS and Standard Material Transfer Agreement (SMTA), to address the relationship of different types of patent claims to Treaty Article 12.3(d), which provides that: “Recipients shall not claim any intellectual property or other rights that limit the facilitated access to [PGRFA], or their genetic parts or components, in the form received from the Multilateral System.”